The second man - Martini, Steve, 1946- (A Paul Madriani novella, 2015)
Navy SEALs are the military's elite, highly trained, deadly, and sworn to secrecy about the details of their dangerous and confidential missions. So when one of the men goes public about a high-profile assassination abroad, all of his comrades are thrown into peril. In this riveting novella, attorney Paul Madriani comes to the aid of a Navy SEAL who is pursued by his own government and facing possible prosecution for disclosures he says were made by others. When the soldier disappears, Paul finds himself ensnared in a deadly game of intrigue that forces him to track the man down before it is too late.